Physiological extracellular electrical signals guide and orient the polarity of gut epithelial cells - Pu, Jin (Tissue Barriers, 2015)
Apical-basal polarity in epithelial cells is a fundamental process in the morphogenesis of many tissues. But how epithelial cells become oriented with functionally specialized luminal and serosal facing membranes is not understood fully. Cell-cell and cell-substrate contacts induce the asymmetric distribution of Na(+)/K(+)-ATPase pumps on basal membrane and are essential for apical-basal polarity formation. Inhibition of the Na(+)/K(+)-ATPase pump abolished apical formation completely. But it is unclear how this pump regulated the apical polarity. We discovered that the transepithelial potential difference (TEP) which is dependent on the basal Na(+)/K(+)-ATPase distribution acts as an essential coordinating signal for apical membrane formation through Ror2/ERK1/2/LKB1 signaling. A similar concept applies to all other ion-transporting epithelial and endothelial tissues and this raises the possibility of regulating the TEP as a therapeutic intervention for disorders in which epithelial function is compromised by faulty electrical signaling.